Rwanda – Beyond Connections : Energy Access Diagnostic Report Based on the Multi-Tier Framework - Koo, Bryan Bonsuk; Rysankova, Dana; Portale, Elisa; Angelou, Niki; Keller, Sandra; Padam, Gouthami (World Bank, Washington, DC, 2018)
A small but densely populated country, Rwanda has one of the fastest growing economies in Sub-Saharan Africa. The Rwandan government is dedicated to expanding access to electricity and aims to increase its electrification rate, first to 70 percent by 2018, and subsequently to 100 percent by 2020 – an ambitious target considering that approximately 86 percent of the country's population resides in rural areas. It's focus on expanding energy access also applies to increasing access to improved cookstoves (ICSs). Rwanda has gained support from multiple development partners to help it reach its energy access goals. Click here for Rwanda's energy access profile and to read the comprehensive Energy Access Country Diagnostic Report.https://energydata.info/dataset/rwanda---multi-tier-framework--mtf--survey--2018-